1996
DOI: 10.1080/02568549609594693
|View full text |Cite
|
Sign up to set email alerts
|

Partner Preferences of British Asian and White Girls and Boys on the Middle School Playground: Do They Vary As a Function of Activity?

Abstract: Abstra ct. A sian and Whit e girls and boys (N=54) were observed on the playground during recess in order to examine their spontaneous peer preferences. All four groups exhi bited a highly signi ficant tend ency to spend more time with own-race, own-gender peers than with any other type ofpeer. Th is result held for the three specific categories ofbehavior that were examined-"R ule Games, ""S ociable," and "Other Play "-with two exceptions (A sian boys did not spend significantly more time with other A sian bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
3
1
Order By: Relevance
“…Each age group communicated with both their ethnic groups and other ethnic groups and native children. This study, therefore, did not correspond with the studies which showed immigrant children preferred their own co-ethnic friendships from pre-school (Finkelstein & Haskins, 1983;Fishbein & Imai, 1993;Leman et al, 2013) to childhood (Boulton, 1996;Leman & Lam, 2008;Verkuyten & Kinket, 2000) and from adolescence to youth (Brüß, 2005;Phinney et al, 1997) rather than inter-group friendships.…”
Section: Tolerant Relationships By Gender-agecontrasting
confidence: 82%
See 1 more Smart Citation
“…Each age group communicated with both their ethnic groups and other ethnic groups and native children. This study, therefore, did not correspond with the studies which showed immigrant children preferred their own co-ethnic friendships from pre-school (Finkelstein & Haskins, 1983;Fishbein & Imai, 1993;Leman et al, 2013) to childhood (Boulton, 1996;Leman & Lam, 2008;Verkuyten & Kinket, 2000) and from adolescence to youth (Brüß, 2005;Phinney et al, 1997) rather than inter-group friendships.…”
Section: Tolerant Relationships By Gender-agecontrasting
confidence: 82%
“…However, it remains unclear how far ethnic group normativity influences children's friendship choices (Leman et al, 2013). Children have higher tendency to play and interact with the same ethnic group from preschool (Finkelstein & Haskins, 1983;Fishbein & Imai, 1993) to childhood (Boulton, 1996;Davey & Mullin, 1982;Leman & Lam, 2008;Leman et al, 2011). Peer relationships provide an important social context for adolescent development (Brechwald & Prinstein, 2011;Meeus, 2011).…”
Section: Racial and Ethnic Categorisation And Friendship Choicesmentioning
confidence: 99%
“…Studies on this topic have documented the presence of ethnic cleavage in children’s friendship and playmate choices. Children’s friendships have been found to delineate along ethnic lines from early childhood (Finkelstein & Haskins, 1983) and clear ethnic differentiation characterizes friendships from middle childhood (Boulton, 1996) through to adolescence (Kao & Joyner, 2004). Thus, children tend to play with ethnic ingroup peers more frequently than with outgroup peers (Davey & Mullin, 1982; Leman et al, 2011) and form more friendships from within their ethnic group than outside it (Aboud, Mendelson, & Purdy, 2003).…”
Section: Ethnic Group Friendshipsmentioning
confidence: 99%
“…These studies, while few in number, converge to suggest that what children do on the playground links in systematic ways to some key parameters of their development (Blatchford, 1998; Boulton, 1999; Hart, 1993; Pellegrini, 1995; Pellegrini & Smith, 1993). For instance, studies have shown that recess provides children with (1) a break that helps optimize subsequent attention to school work (Smith & Hagen, 1980; see Pellegrini & Bjorklund, 1996), (2) opportunities to develop social relationships (Blatchford, 1998; Boulton, 1996), and (3) opportunities to develop social skills (Sluckin, 1981; Sutton‐Smith, 1971).…”
mentioning
confidence: 99%